PS 02-63 CORRELATION OF AMBULATORY BLOOD PRESSURE PARAMETERS AND THE LEFT VENTRICULAR END-DIASTOLIC PRESSURE DURING LEG-RAISE EXERCISE. (September 2016) - Choi, SeongIl; Park, Whoan Cheol; Kim, Soon Gil; Shin, Jinho
Abstract : Objective: LVEDP is determined by pulse rate (PR), preload, and afterload etc., which are also blood pressure (BP)-determining factors. As a result, LVEDP is more likely to be associated with ambulatory blood pressure monitoring (ABPM) parameters. However, little is known of relationship between ABPM parameters and LVEDP. Thus, this study investigated how ABPM parameters were associated with the LVEDP during leg-raise. Design and Method: 134 euvolemic patients with exertional dyspnea underwent left cardiac catheterization, coronary angiography, echocardiography and ABPM during same admission. In patients with non-significant coronary stenosis and normal ejection fraction, the leg-raise was performed as 2 stages during left cardiac catheterization. Results: LVEDP at rest was mainly correlated with PR parameters (i.e. average real variability (ARV) of PR at wake, ARV of 24-hour PR, standard deviation (SD) of PR at wake, and SD of 24-hour PR). Although LVEDP at leg-raise showed the correlation with PR parameters (i.e. ARV of 24-hour PR, ARV of PR at wake, ARV of PR at sleep, mean PR at wake, mean 24-hour PR, SD of 24-hour PR, SD of PR at wake, and SD of PR at sleep), pulse pressure (PP) was also well correlated with LVEDP values at leg-raise (mean PP at wake and mean 24-hour PP). When the increased LVEDP at rest was defined as > 15 mmHg, SD of PP at wake and 24 hours were significantly higher in the increased LVEDP. Likewise, when the increased LVEDP at leg-raise was defined as > 18 mmHg, the increased LVEDP group had significantly higher values of PP and SBP at wake and 24 hours. Conclusions: Although PR was most commonly correlated with LVEDP, LVEDP at leg-raise was chiefly associated with PP and SBP at wake and 24 hours. It means that PP at wake may play an important role in the LVEDP hemodynamics.